A Submersible Power Station: Part A Helium Power Conversion Unit - Jon Serna; Eduardo Anselmi Palma; Stefania Romero; Dimitrios Fouflias; Pericles Pilidis (Journal of Marine Science and Engineering)
Nuclear power continues to hold great promise in the green revolution, however public opinion regarding its deployment is mixed. A submersible nuclear power station concept is presented here that is expected to allay many concerns that are holding back the growth of nuclear power. This submersible can move under its own power during emergencies and routine maintenance. Being stationed at sea it is earthquake proof. In the case of a tsunami it could decouple from the coast and sail to a location several miles to deeper waters in less than 30 min. Furthermore, it could be built, commissioned, maintained, refueled and scrapped in a country like the UK. This makes it proliferation-proof, a key concern with the wider deployment of nuclear power. In the present evaluation the philosophy and the electric power generation capability of the submersible power station are investigated. This includes a pre-feasibility visualization of the design. An evaluation is carried out into fitting it in a submersible of a size similar to the largest existing nuclear submarines. These designs may enable it to deliver 0.6 to 1 GW of electrical power.